2020
DOI: 10.33890/innova.v5.n3.2.2020.1568
|View full text |Cite
|
Sign up to set email alerts
|

Sistema experto para la SGTI en la empresa Sion Global Solutions

Abstract: En la empresa, se determinó que el nivel de madurez, en relación a la ejecución de los sistemas, es imperfecto, porque hay poca confianza, un menor nivel de eficiencia, y los lapsus resaltan lo acordado. En este sentido, el objetivo de la investigación fue demostrar en qué medida un sistema experto mejora la Gestión de Servicios de TI en la Sion Global Solution Company en el tiempo esperado, los niveles de confiabilidad y la efectividad en las evaluaciones de los niveles de madurez en la gestión de servicios i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Talent management seeks the growth and engagement of human capital by elevating their competencies. The companies' level of excellence focuses on customer satisfaction and the development of employee competencies through performance, selection, training and compensation practices (Flores Zafra and Gardi Melgarejo, 2020; Burke and Morley, 2023). This fact enables employees to increase their commitment to the organization and to increase the quality of service offered to customers (Hernández Junco and Santamaría, 2018).…”
Section: Literature Review: Antecedents Of Service Qualitymentioning
confidence: 99%
“…Talent management seeks the growth and engagement of human capital by elevating their competencies. The companies' level of excellence focuses on customer satisfaction and the development of employee competencies through performance, selection, training and compensation practices (Flores Zafra and Gardi Melgarejo, 2020; Burke and Morley, 2023). This fact enables employees to increase their commitment to the organization and to increase the quality of service offered to customers (Hernández Junco and Santamaría, 2018).…”
Section: Literature Review: Antecedents Of Service Qualitymentioning
confidence: 99%
“…Expert systems are therefore very important to organisations as an effective means of managing management plans. [5][6][7] According to the study carried out by, 5 the effectiveness of Expert Systems was determined in the Information Technology Management System of the company Sion Global in Peru. They concluded that ES have the potential to be used by companies because they can control the quality of services throughout the process.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that ES have the potential to be used by companies because they can control the quality of services throughout the process. 5 On the other hand, 6 want to understand the principles of expert systems and in turn provide the right communication and information for system development. As a result, they found that the tests performed coincided in correcting all the errors, so they were presented well and without any problems.…”
Section: Introductionmentioning
confidence: 99%
“…In Bolivia ( Alvarado-Gisbert, 2020 ), it was shown that it is crucial for students to be guided with vocational training, taking into account their professional profile, as well as having the necessary information about the academic offer, the work scenario, the demands and requirements of each career, which allows the student to plan their professional future. In Peru ( Flores & Gardi, 2020 ) it has been shown that the implementation of an expert system for the SGTI in a company manages to optimise the average time for the evaluation of the maturity levels, optimising the levels of reliability and efficiency. In Peru ( Barzola & Flores, 2017 ), the implementation of an Expert System for Vocational Guidance Support applied in an educational institution achieved great support in reducing the total time of the vocational guidance process, the total time of the analysis of the vocational test and increasing the total time of the interview with the student, fulfilling the purpose of supporting the work of the counsellor and the student.…”
Section: Introductionmentioning
confidence: 99%